Phase equilibria in three component systems alcohol-hydrocarbon-water - Siswana, Msimelelo Patrick (Rhodes University, Faculty of Science, Department of Chemistry, 1992)
The fuel industry in many parts of the world is blending alcohols with motor fuel either to extend the fuel or to improve its octane rating or both. Unfortunately alcohols are hygroscopic and as a result, water becomes a component of the fuel. This can lead to phase separation and the formation of a water-rich layer which could have serious corrosion consequences. In an attempt to understand the phase-splitting in alcohol-petrol-water blends, phase equilibria in ternary systems (alcohol-hydrocarbon-water) have been determined by experiment. The phase equilibria in these ternary systems are also discussed in terms of modern theories of liquid mixtures and the UNIQUAC theory is applied to the "ethanol + benzene + water" ternary system. The alcohols are all the Câ‚ , Câ‚‚, Câ‚ƒ and Câ‚„ alcohols, and the hydrocarbons include those typically found in petrol, e.g. cyclohexane, benzene and substituted benzenes.
Keywords: Chemical equilibrium; Liquid-liquid equilibrium; Alcohol as fuel; Hydrocarbons; Water chemistry